Prevalence of Corneal Astigmatism in Patients before Cataract Surgery in Northern China - Xiaoyong Yuan; Hui Song; Gang Peng; Xia Hua; Xin Tang (Journal of Ophthalmology)
Purpose. To analyze the prevalence and presentation patterns of corneal astigmatism in cataract surgery candidates in a teaching hospital in northern China. Methods. From May 1, 2012, to April 30, 2013, partial coherence interferometry (IOLMaster) measurements of all qualified cataract surgery candidates were retrospectively collected and analyzed. Results. The study evaluated 12,449 eyes from 6,908 patients with a mean age of 69.80±11.15 (SD) years. The corneal astigmatism was 0.5 diopters (D) or less in 20.76% of eyes, 1.0 D or more in 47.27% of eyes, 2.0 D or more in 13.16% of eyes, and 3.0 D or more in 3.75% of eyes. With-the-rule astigmatism was found in 30.36% of eyes, while against-the-rule was found in 52.41% of eyes. The percentage of against-the-rule astigmatism increased with age. Conclusion. Our study showed that almost one-half of preoperative eyes (47.27%) in northern China have a corneal astigmatism of 1.0 D or more, indicating that more surgical techniques or toric IOLs are needed to achieve better visual rehabilitation.